Individual and Community Perspectives, Attitudes, and Practices to Mother-to-Child-Transmission and Infant Feeding among HIV-Positive Mothers in Sub-Saharan Africa: A Systematic Literature Review - Alexander Suuk Laar, MPH; Veloshnee Govender, MPH (Global Health and Education Projects, Inc., 2013)
Objectives: International guidelines on infant feeding for HIV-positive mothers promote Exclusive Replacement Feeding (ERF) (infant formula or animal milk) or exclusive breastfeeding (with no supplements of any kind). A mixed feeding pattern, where breastfeeding is combined with other milks, liquid foods or solids, has been shown to increase the risk of transmission of HIV and is strongly discouraged. However, little is known about the ability of women to adhere to recommended feeding strategies to prevent mother-to-child transmission (MTCT) of HIV from breast milk. The objective of this study was to assess the individual and community-level factors that affect perspectives, attitudes and practices of HIV-positive mothers on MTCT and infant feeding in sub-Saharan Africa as documented in peer-reviewed and grey literature. Methods: This work is based on an extensive review of peer-reviewed articles and grey literature from the period 2000-2012. The literature search was carried out using electronic databases like, Medline Ovid, Google scholar, Pubmed and EBSCOhost. Both quantitative and qualitative studies written in English language on HIV and infant feeding with particular emphasis on sub-Saharan Africa were included. Results: The review found low adherence to the chosen infant feeding method by HIV-positive mothers. The following factors emerged as influencing infant feeding decisions: cultural and social norms; economic conditions; inadequate counselling; and mother's level of education. Conclusions and Public Health Implications: Unless local beliefs and customs surrounding infant feeding is understood by policy makers and program implementers, Prevention of Mother-to-Child Transmission (PMTCT) programs will only be partially successful in influencing feeding practices of HIV-positive women. Hence programs should provide affordable, acceptable, feasible, safe and sustainable feeding recommendations that do not erode strong cultural practices. Advice to HIV-positive mothers should be based on local conditions that are acceptable to the community.